Hypertrophic cardiomyopathy with dynamic obstruction and high left ventricular outflow gradients associated with paradoxical apical ballooning. Issue 1 (12th December 2018) - Sherrid, Mark V.; Riedy, Katherine; Rosenzweig, Barry; Ahluwalia, Monica; Arabadjian, Milla; Saric, Muhamed; Balaram, Sandhya; Swistel, Daniel G.; Reynolds, Harmony R.; Kim, Bette
Abstract : Background: Acute left ventricular (LV) apical ballooning with normal coronary angiography occurs rarely in obstructive hypertrophic cardiomyopathy (OHCM); it may be associated with severe hemodynamic instability. Methods, Results: We searched for acute LV ballooning with apical hypokinesia/akinesia in databases of two HCM treatment programs. Diagnosis of OHCM was made by conventional criteria of LV hypertrophy in the absence of a clinical cause for hypertrophy and mitral‐septal contact. Among 1519 patients, we observed acute LV ballooning in 13 (0.9%), associated with dynamic left ventricular outflow tract (LVOT) obstruction and high gradients, 92 ± 37 mm Hg, 10 female (77%), age 64 ± 7 years, LVEF 31.6 ± 10%. Septal hypertrophy was mild compared to that of the rest of our HCM cohort, 15 vs 20 mm ( P < 0.00001). An elongated anterior mitral leaflet or anteriorly displaced papillary muscles occurred in 77%. Course was complicated by cardiogenic shock and heart failure in 5, and refractory heart failure in 1. High‐dose beta‐blockade was the mainstay of therapy. Three patients required urgent surgical relief of LVOT obstruction, 2 for refractory cardiogenic shock, and one for refractory heart failure. In the three patients, surgery immediately normalized refractory severe LV dysfunction, and immediately reversed cardiogenic shock and heart failure. All have normal LV systolic function at 45‐month follow‐up, and all have survived. Conclusions: Acute LV apical ballooning, associated with high dynamic LVOT gradients, may punctuate the course of obstructive HCM. The syndrome is important to recognize on echocardiography because it may be associated with profound reversible LV decompensation.